Synthesis and characterization of the thermal and the solvatochromic properties of heterocyclic azo dyes derived from 5-N,N-dialkylamino-2,2´-bithiophene couplers - Raposo, M. Manuela M. (2009)
A series of heterocyclic azo dyes was synthesized by diazotation of several substituted anilines and coupling with 5-N,N-dialkylamino-2,2´-bithiophenes to give 4-phenylazo-5-N,N-dialkylamino-2,2´-bithiophenes 4-7. This reaction contrasts with the behavior of 5-alkoxy-2,2´-bithiophenes towards aryldiazonium salts which gave 5-phenylazo-5-alkoxy-2,2´-bithiophenes. The thermal stability of the derivatives was evaluated using thermogravimetric analysis. The solvatochromic behaviour of the novel bithiophene azo dyes was investigated in several solvents of different polarity. The experimental results indicate that, the heterocyclic azo dyes 4-7 could be used as thermally stable solvatochromic probes.